Factors affecting the level of farmer participation in the agricultural extension services of cereal production in Bhutan - Bahadur Shangshon, Bhakta; Polthanee, Anan; Suriya, Patcharee (วารสารแก่นเกษตร, 2023)
The purposes of this study were to assess the participation level of cereal farmers in agricultural extension services in Bhutan and to examine the factors affecting their participation. Data were collected by interviewing 251 farmers with a simple random sampling method from eight Gewogs (a group of villages), selected from four districts; consisting of the western, northern, southern, and eastern regions of Bhutan. Descriptive statistics were employed to analyze socioeconomic characteristics and the participation levels in extension services of the farmers. In addition, Chi-square statistics were used to examine the factors influencing the farmers’ participation in extension services. The results determined that the participation in extension services of cereal farmers was generally low in Bhutan, with most accessing services through home visits, training, and mobile phone communication. Analysis of the relevant socioeconomic factors found that several factors influenced the participation of farmers in various extension service methods. In particular, the district where the farmers lived had a significant relationship with their participation in in-home visits, group discussions, and mobile phone communication. Age was also a significant factor in participation in in-home visits, mobile phone communication, and demonstrations. The total cultivated land owned by the farmers was significantly related to their participation in in-home visits, group discussions, and demonstrations. Gender was significantly associated with the farmers' participation in information sharing through TV or radio, while education level was directly related to their participation in study tours. Lastly, changes in production costs affected farmers' participation in training. Based on these findings, we suggest that agricultural extension service methods should be customized to meet the specific needs of farmers based on their socioeconomic contexts.